(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
تتميّز رسوبيات البليوسين البحريّة في حوض نهر الكبير الشماليّ بصعوبة متابعتها بدقّة، وذلك بسبب ثخانتها الكبيرة وتشابهها الليتولوجي، وقد مكّنت المقاطع المدروسة في هذا البحث وعددها (6) ستة مقاطع بإجراء وصف ليتولوجي تفصيلي لهذه الرسوبيات التي تتألف من المارل، والمارل الغضاري إلى الغضار الكلسي متنوع التطبق، مع تداخلات من الحجر الكلسي الرملي ، أو الحجر الكلسي الحطامي العضوي، كما سمحت التحاليل المكروباليونتولوجية للعينات المأخوذة وعددها (91) عينة، اعتماداً على الأنواع البلانكتونية بالتعرّف على النطاقات الرئيسة للبليوسين الأدنى، فقد تمّ تمييز النطاقين الرئيسين للبليوسين الأدنى وهما: النطاق العلوي: Globorotalia margaritae evoluta والنطاق السفلي Sphaeroidinollopsis Acme، وإجراء مضاهاة بين المقاطع المدروسة في مواقع مختلفة في حوض نهر الكبير الشمالي. The MariniPeliocene depositions in theNahr AL-Kabir Al-Shimali Basin is distinguished by the difficulty of following them because of their considerable thickness and their litological resemblance. The studied sections in this study – six sections – enabled conducting detailed litological description for these depositions which consist of marl and clay marl to the different positioning lime clay with interference of sand limestone or organic debris limestone. The micropaliontologic analysis for the samples – ninety – one samples – based on the planktonic species enabled identifying the major zones of the peliosene were recognized they are two major zones of lower peliocene: the upper zone Globorotalia amargaritae evoluta and lower zone Sphaeroidinollopsis Acme, and conducting connection between the studied sections in different positions in Nahr AL-Kabir Al-Shimali Basin.